(untitled) (Washington DC, 2006)
In the early 2000s, the government of Sri Lanka considered engaging private operators to manage water and sewerage services for two separate service areas that spanned the districts of Gampaha, Kalutara, and Galle. To better inform the design of these private sector transactions, we surveyed 1,800 households in southwest Sri Lanka and created spatial maps of poverty and network services. Our maps and models lead us to four conclusions. First, poor and non-poor households have different behaviors regarding water and sanitation, which affects the distributional impacts of the proposed private sector participation (PSP) transactions.
Keywords: Water supply,Sanitation,Cung cấp nước; Sri Lanka,Sri Lanka,Sri Lanka